Knowledge, Attitude, And Practice Of Endocrown In Post- Endodontic Management Among General Practitioners - RASIDI, MOHAMAD QULAM ZAKI BIN MOHAMAD; ANTHONY, S. DELPHINE PRISCILLA; PRABU, DINESH (The journal of contemporary issues in business and government, 2021)
Postendodontic treatment management consists of restoration that should give protection and preservation of remaining tooth structure while giving satisfactory aesthetics appearance, its form, and good function. The endocrown consists of a single unit with a circular butt-joint finish line and a central retention cavity inside the pulp chamber. The goal of endocrown usage is to achieve minimally invasive preparations and to conserve the existing tooth structure. The aim of this survey was to assess the level of awareness and the current state of knowledge and opinions toward endocrown as one of postendodontic management in practice amongst dental practitioners. This cross-sectional study was done among dental interns and practitioners from various institutions in Chennai. A total of 120 participants took part in this survey study. Results were analysed and compared using the SPSS Statistical Software by doing both the frequency tests and correlation tests. More than half of dental practitioners (55.83%) reported that they were aware of the use of endocrown as one of the post endodontics management. However, only 27.5% said that they had practised the use of endocrown during their training. Within the limits of the study, dental practitioners commonly have less training and practice in management of post endodontics restoration using endocrown. In regard to their knowledge, they showed an acceptable level of knowledge and awareness of usage of endocrown as one of post endodontics management.